Penerapan Teori Belajar Konstruktivisme dalam Pembelajaran IPS di SD - Sintya, Desti Dewi; Prastiwi, Dinda Astria; Khansa, Tania Puti; Marini, Arita; Yunus, Mahmud (Sindoro: Cendikia Pendidikan, 2024)
This article discusses the importance of applying constructivist learning theory in social studies education at the elementary school level. This theory emphasizes the active role of students in constructing their own knowledge and understanding through experience and interaction with their environment. In the context of social studies education, constructivist learning theory encourages students to explore, analyze, and apply knowledge in real life situations, not just memorize facts. This article uses a descriptive method, with data collection carried out through literature study using references to books and journals that are relevant to the topic being studied. The results and discussion of this research explain that the knowledge construction process takes longer and may be difficult for students who need more structured guidance. Nevertheless, constructivism theory remains an important approach in social studies education in elementary schools, because it is able to equip students with useful skills to understand and contribute to their social life. Artikel ini membahas tentang pentingnya penerapan teori pembelajaran konstruktivis dalam pendidikan IPS tingkat sekolah dasar. Teori tersebut menekankan peran aktif siswa dalam mengkonstruksi pengetahuan dan pemahamannya sendiri melalui pengalaman dan interaksi dengan lingkungannya. Dalam konteks pendidikan IPS, teori belajar konstruktivis mendorong siswa untuk mengeksplorasi, menganalisis, dan menerapkan pengetahuan dalam situasi kehidupan nyata, bukan sekadar menghafal fakta. Artikel ini menggunakan metode deskriptif, dengan pengumpulan data dilakukan melalui studi kepustakaan dengan menggunakan referensi buku-buku dan jurnal yang relevan dengan topik yang dikaji. Hasil dan pembahasan dari penelitian ini menjelaskan bahwa Proses konstruksi pengetahuan memerlukan waktu yang lebih lama dan mungkin sulit bagi siswa yang membutuhkan panduan lebih terstruktur. Meskipun demikian, teori konstruktivisme tetap menjadi pendekatan penting dalam pendidikan IPS di SD, karena mampu membekali siswa dengan keterampilan yang berguna untuk memahami dan berkontribusi dalam kehidupan sosial mereka.